ASSUNÇÃO, Ronaldo. Mário de Andrade e Jorge Luis Borges: poesia, cidade, oralidade. Campo Grande: Ed. UFMS, 2004. 292 p. - Santos, Rosana Cristina Zanelatto (Diálogos Latinoamericanos, 2005)
ASSUNÇÃO, Ronaldo. Mário de Andrade e Jorge Luis Borges: poesia, cidade, oralidade. Campo Grande: Ed. UFMS, 2004. 292 p.